Umerjanje in preverjanje geometrijske natančnosti računalniško krmiljenih obdelovalnih strojev - Cedilnik, Marko (Strojniški vestnik, 2006)
Constant computer-hardware and software developments have resulted in enhancedrequirements for the dimensional accuracy of products. An accurate product reflects the geometrical accuracy of the CNC machine-tool. A quick accuracy test of a CNC machine-tool can be performed with the Ballbar QC10 device; calibration and parameter correction on the CNC controller can be done with a test-result analysis from the very accurate ML10 laser device. In this paper a brief overview of the working principles of the Ballbar QC10 device is presented. Some of the parameters that are directly related to the accuracy level of the CNC machine-tool are described in detail.
Keywords: CNC stroji; natančnost; preizkušanje